Book review: Christian mission in a diverse British urban context: Crossing the racial barrier to reach communities - D.N. Andrew (Acta Theologica)
A book review of "Christian mission in a diverse British urban context: Crossing the racial barrier to reach communities" by Afrane-Twum, J.A. (Langham Publishing, 2024), 213 pages, ISBN: 978-1-83973-875-3.